The Role of Financial Socialization and Psychological Factors in Shaping Personal Financial Management Behavior among Young Professionals - Eka Sri Wahyuni; Katiya Nahda (International Journal of Economics, Business and Innovation Research, 2025)
Personal financial literacy acts as a crucial factor in shaping individual financial management behavior, primarily through financial socialization processes from various sources such as parents, peers, and media. This study aims to identify the extent to which financial socialization and psychological factors—such as financial attitudes, locus of control, and self-control—influence personal financial management among young professionals. Utilizing a quantitative approach and survey method, data were collected from young professionals aged 25 to 40 years using purposive sampling. Analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine relationships among financial socialization, psychological factors, and financial behavior, with financial literacy assessed as a mediating variable. The findings suggest that both financial socialization from family, peers, and media, as well as psychological constructs, significantly impact financial management behavior, but the mediating effect of financial literacy is essential to translate these socializations into positive financial practices. Implications of this research bear relevance for theoretical development as well as practical initiatives by educators and policymakers aiming to foster healthy financial behaviors among young professionals.